2020
DOI: 10.1002/ecy.3180
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of a large herbivore changes regulation of seagrass productivity in a naturally grazed Caribbean ecosystem

Abstract: Recovery of a large herbivore changes regulation of seagrass productivity in a naturally grazed Caribbean ecosystem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 89 publications
(180 reference statements)
0
42
2
Order By: Relevance
“…However, some of these studies were conducted at subtropical/temperate latitudes, near the northern limit of the T. testudinum range (Fourqurean et al., 2010; Holzer & McGlathery, 2016). Other studies from tropical Caribbean locations found no difference in below‐ground biomass (Gulick et al., 2020; Johnson et al., 2017) or storage of rhizome soluble carbohydrates (Gulick et al., 2020) between naturally grazed and ungrazed areas. Since light availability and depth are critical to supporting below‐ground biomass (Enríquez et al., 2019) and the storage of carbohydrates in seagrasses (Alcoverro et al., 2001; Lee & Dunton, 1997), we propose that the increase in light availability in grazed areas and the tropical latitude could collectively play a role in the sustained below‐ground biomass in grazed areas at our study site.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…However, some of these studies were conducted at subtropical/temperate latitudes, near the northern limit of the T. testudinum range (Fourqurean et al., 2010; Holzer & McGlathery, 2016). Other studies from tropical Caribbean locations found no difference in below‐ground biomass (Gulick et al., 2020; Johnson et al., 2017) or storage of rhizome soluble carbohydrates (Gulick et al., 2020) between naturally grazed and ungrazed areas. Since light availability and depth are critical to supporting below‐ground biomass (Enríquez et al., 2019) and the storage of carbohydrates in seagrasses (Alcoverro et al., 2001; Lee & Dunton, 1997), we propose that the increase in light availability in grazed areas and the tropical latitude could collectively play a role in the sustained below‐ground biomass in grazed areas at our study site.…”
Section: Discussionmentioning
confidence: 92%
“…Light attenuation coefficients within the seagrass canopy (Canopy‐K d , m −1 ), a metric for the degree of leaf self‐shading, were calculated for each exclosure (see Enríquez et al., 2019; Enríquez & Pantoja‐Reyes, 2005). In situ grazing intensity was calculated at the time of exclosure placement, using the following index (ranges from 0 to 1, or 0%–100% removal of blade biomass; Gulick et al., 2020):Grazingintensity0.333333em=#Grazed0.277778emshootsfalse/m2#Total0.277778emshootsfalse/m2×Ungrazed0.277778emblade0.277778emlengthGrazed0.277778emblade0.277778emlengthUngrazed0.277778emblade0.277778emlength.Grazing intensity ranged from 0.1 to 0.7 at our study site (Gulick et al., 2020); allowing for a thorough assessment of relationships between T. testudinum growth and morphology and the canopy light environment over a gradient of in situ grazing pressure in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Foraging green turtles exert pressure on seagrass densities and health over time-both positively through grazing (Gulick et al 2020(Gulick et al , 2021 and negatively by consuming large patches of seagrass (Heithaus et al 2014;Gangal et al 2021). Since the discovery of the large densities of green turtles in the Lakshadweep archipelago of India (Tripathy et al Gangal et al (2021) found that green turtle densities reached numbers above what seagrass beds on the foraging grounds can support.…”
Section: Discussionmentioning
confidence: 99%